PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Jaya Kirana; Nurmatias Nurmatias (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2014)
This research aims to investigate the influence of firm performance and good corporate governance on firm value and investigate the interaction firm performance with good corporate governance. This study take 334 sample financial reporting of listed firm on Bursa Efek Indonesia in year 2012. The results showed that the index corporate governance (ICG), firm performance of ROA and ROE have not significant effect to of firm value PBV. But give significant positive effect if index corporate governance interacted with firm performance on firm value PBV.